Effect of the zinc phthalocyanine mediated photodynamic therapy on cytoskeletal apparatus of hela cells - Hošíková, Barbora; Binder, Svatopluk; Lenobel, René; Malohlava, Jakub; Hošík, Jakub; Jiravová, Jana; Malina, Lukáš; Zapletalová, Jana; Kolářová, Hana (Lékař a technika, 2019)
Photodynamic therapy is a very promising and constantly evolving diagnostic and therapeutic method that is used mainly for malignant and non-malignant tumors treatment. This study deals with the utilization of zinc photosensitizer (λmax ~ 660 nm) from the group of phthalocyanines in photodynamic therapy. The aim of this study is to evaluate in vitro effect of the 5 Jcm-2 zinc phthalocyanine photosensitizer-mediated photodynamic therapy in EC50 concentration (30 nM) on cytoskeletal apparatus of the tumor cell line-HeLa (cervical cancer cells). For the measurement, the tandem mass spectrometry, atomic force and fluorescent confocal microscopy techniques were used. The results showed, that compared to the control cells zinc-derivative mediated photodynamic therapy caused in HeLa cells significant change of the cell height and extensive cytoskeletal actin rearrangement although the levels of beta actin, gamma actin and F-actin did not change significantly. This is probably caused by decreased level of the ARPC2 actin-related protein which is responsible for actin polymerization. Its level decreased 24 hours after therapy by 56%. The cytoskeletal apparatus is one of the basic cellular structures that provides cell shape, cell division and the intracellular transport. After in vitro 5 Jcm(-2) zinc derivative-mediated photodynamic therapy, the cervical carcinoma cells showed a significant damage of the cytoskeletal structure followed by changes of cell shape leading to cell death. Considering these results and low effective concentration (EC50 = 30 nM), the therapy used is potentially very promising antitumor treatment.
Keywords: Research; reaktivní formy kyslíku; Cytoskeleton; výzkum; lidé; Photochemotherapy; Tumor Cells, Cultured; fotochemoterapie; Reactive Oxygen Species; nádorové buňky kultivované; cytoskelet; Humans